Improvement of plant performance under water deficit with the employment of biological and chemical priming agents. (9th March 2018) - Balestrini, R.; Chitarra, W.; Antoniou, C.; Ruocco, M.; Fotopoulos, V.
Abstract: Drought represents one of the major constraints on agricultural productivity and food security and in future is destined to spread widely as a consequence of climate change. Research efforts are focused on developing strategies to make crops more resilient and to mitigate the effects of stress on crop production. In this context, the use of root-associated microbial communities and chemical priming strategies able to improve plant tolerance to abiotic stresses, including drought, have attracted increasing attention in recent years. The current review offers an overview of recent research aimed at verifying the role of arbuscular mycorrhizal fungi and chemical agents to improve plant tolerance to drought and to highlight the mechanisms involved in this improvement. Attention will be devoted mainly to current knowledge on the mechanisms involved in water transport.